Biomass derived carbon/platinum nanoparticles as electrocatalyst for the hydrogen evolution - Shimaa M. Ali (Scientific Reports)
Abstract Green hydrogen is gaining a significant attention in the transition to sustainable energy and achieving net-zero emissions. Platinum-based catalysts are highly regarded in hydrogen production, particularly due to their efficiency in water electrolysis. Platinum nanoparticles (Pt NPs) is successively prepared by the microwave-assistant citrate method on a biomass-based support, and characterized by X-rays diffraction, scanning and transmission electron microscopy. The chelation and gelation resulted by using citric acid during the synthesis lead to the formation of highly stabilized and dispersed Pt NPs on the carbon support. The electrocatalytic activity of Pt NPs for the hydrogen evolution reaction (HER) is examined by cathodic linear polarization and impedance spectroscopy. A high catalytic performance is shown by the prepared sample, as indicated by the calculated exchange current density 5.3 mA/cm2, and activation energy, 38.13 kJ/mol. The HER follows Volmer/Tafel mechanism with a reaction order of unity. Impedance spectra confirms the high electrocatalytic activity by the decrease of the total impedance, pore resistance, and charge-transfer resistance, with increasing the applied overpotential. The proposed synthesis method offers a green, economic, and efficient route for preparing precious metals used for catalytic applications.